Benefiting from binary negations? Verbal negations decrease visual attention and balance its distribution - Banh, Ngoc Chi; Tünnermann, Jan; Rohlfing, Katharina J.; Scharlau, Ingrid (Frontiers in Psychology, 2024)
Negated statements require more processing efforts than assertions. However, in certain contexts, repeating negations undergo adaptation, which over time mitigates the effort. Here, we ask whether negations hamper visual processing and whether consecutive repetitions mitigate its influence. We assessed the overall attentional capacity, that is, the available processing resources, and its distribution, the relative weight, quantitatively using the formal Theory of Visual Attention (TVA). Here, we employed a very simple form for negations, binary negations on top of an accuracy-based, TVA-based temporal-order judgment (TOJ) paradigm. Negated instructions, expressing the only alternative to the core supposition, were cognitively demanding, resulting in a loss of attentional capacity in three experiments. The overall attentional capacity recovered gradually but stagnated at a lower level than with assertions, even after many repetitions. Additionally, negations distributed the attention equally between the target and reference stimulus. Repetitions slightly increased the reference stimulus’ share of attention. Assertions, on the other hand, shifted the attentional weight towards the target stimulus. Few repetitions slightly decreased the attentional shift towards the target stimulus, many repetitions increased it